THERMAL ANALYSIS AND MICROSTRUCTURAL STUDY OF POROUS β-TiNb INCORPORATED WITH TiH2 POWDER VIA LOW-COST PROCESSING ROUTE - Hosnie, S.M.; Yahaya, M.; Haris, N.A.; Ismail, M.H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
In the development of Ti-based alloy bio-implant material, Titanium Hydride (TiH2) which is commonly used as a pore former agent has become one of the new approaches of starting material via powder metallurgy processing route with the aim of low-cost production in the fabrication of Beta-typed Titanium Niobium (β-TiNb) alloy. However, the thermal behaviour of TiNb alloy by TiH2 substitution is still not well understood. Thus, in the present work the compacted of Ti and Nb mixture was subjected to thermal analysis via differential thermal analysis (DTA) and dilatometry to evaluate thermal events existed during sintering process. It was found that the overall reaction had undergone four-step processes; the first two steps were subjected to the dehydrogenation process whereas the last two steps corresponded to the formation of TiNb alloy. In addition, the β phase of TiNb exhibited better appearance at 1200°C sintered temperature which was supported by X-ray Diffraction (XRD) analysis.